PEMETAAN CABANG PERUSAHAAN ASURANSI X BERDASARKAN LAPORAN BEBAN KLAIM DAN PENERIMAAN PREMI MENGGUNAKAN BIPLOT - Maharani Febriana Putri; Yuciana Wilandari; Rita Rahmawati (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
The number of cars currently make everyone aware of the benefits of insurance to protect against financial loss. Insurance products that demand a lot of people are motor vehicle insurance product that car. As an entrepreneur it is necessary to determine whether or not a company healthy in order to determine the condition of the company and what things need to be considered to improve the financial condition of the company. To see healthy or not an insurance company then needs to be analyzed on the income and expenditures of the company. The company has a good insurance premium income is greater than the burden of claims. This makes the company should strive to find that a lot of customers and minimize the burden of the claims that the company is in good financial condition. This study was conducted to find out how the condition of the company by using biplot analysis. This analysis can be applied to determine the company branch mapping, information and determine which branch company has the top achievers. The results obtained from these studies is the premium income report greater than the burden of claims and the top achievers is Surabaya Tunjungan. In addition, mapping that can be explained by a biplot analysis reached 100% which means it can explain the total data properly.Keywords : company branch mapping, biplot analysis, premium income and burden of claims